All-Optical Photonic Microwave Phase Shifter Requiring Only a Single DC Voltage Control - T. Li; E. H. W. Chan; X. Wang; X. Feng; B. Guan (IEEE Photonics Journal)
An all-optical photonic microwave phase shifter that requires only a single dc voltage control to realize continuous 0° to 360° radio-frequency (RF) signal phase shift over a wide frequency range is presented. It is based on using an integrated dual-parallel Mach Zehnder modulator (DPMZM) with a 90° polarization rotator in one arm to generate an orthogonally polarized optical carrier and RF modulation sidebands and using a polarization-dependent optical phase shifter to introduce different optical phase shifts to these orthogonal polarization components. The phase shifter has a fast response time, a high resolution, and a compact structure. Experimental results are presented, which demonstrate a continuous 360° phase shift with a flat phase and amplitude response performance over a microwave frequency range of 6.5–26.5 GHz.